Young Heart Health: A Call for Early Prevention and National Vigilance - Joshi, Rheecha; Mahaju Bajracharya, Smriti; Joshi, Dikshya (Nepalese Heart Journal, 2025)
Cardiovascular disease is increasingly affecting the younger population in Nepal, representing a dual burden of rheumatic and lifestyle-related disorders. Rheumatic heart disease continues to impose significant morbidity among school-aged children, particularly in underserved regions, while premature ischemic heart disease is rising among young adults due to smoking, stress, physical inactivity, and poor dietary habits. Early, integrated prevention is essential to address this evolving epidemic. Strengthening school-based screening and prophylaxis programs for rheumatic disease, promoting healthy lifestyle behaviors, and incorporating regular cardiovascular risk assessment in educational and occupational settings are key strategies. National policies aligned with WHO noncommunicable disease targets can enhance coordination and sustainability of these efforts. Protecting young heart health is not only a medical responsibility but a national imperative vital for preserving the productivity and future of Nepal’s youth.